Ordering knowledge in the roman empire - Konig, Jason (Cambridge University Press, 2013)
We are grateful to the Master and Fellow of St John’s College, Cambridge, for funding of the December 2001 conference on which this volume is based; and to all who participated in that event. We would also like to thankMichael Sharp and Sarah Parker at Cambridge University Press, and the anonymous readers for the volume; and also colleagues at Cambridge, Exeter and St Andrews, many of them working on related projects, for ideas and support (within the Exeter Centre for Hellenistic and Romano-Greek Studies and the St Andrews Logos Centre for study of ancient systems of knowledge)